Duas novas espécies do gênero Polymerus Hahn, 1831, no Brasil (Hemiptera, Miridae, Mirini) - Fiuza Ferreira, Paulo Sérgio (Revista Ceres, 2025)
The author, describes two new species of the genus Polymerus Hahn, 1831 (Miridae, Mirini) from Brazil, as follows: Polymerus aristeae n.sp., Rondônia, Minas Gerais and Santa Catarina; Polymerus minutus n.sp., Minas Gerais, Rio de Janeiro, São Paulo, Paraná and Santa Catarina. Illustrations of the new species and genitalia are included.